2011
DOI: 10.1094/ats-2011-0926-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Cultivars Differ in Their Summer Traffic Tolerance and Ability to Maintain Green Turf Coverage Under Fall Traffic

Abstract: Bermudagrass [Cynodon spp. (L.) Rich.] is one of the most widely used turfgrass species for golf courses and sports fields in the southern United States and in the transitional climatic zone. Continuous trafficking from play or equipment can reduce bermudagrass coverage and turf quality. This study evaluated 42 bermudagrass cultivars for their response to traffic. Traffic was applied in summer and fall of 2007 and 2008 with a Cady Traffic Simulator. There were several commercially available cultivars that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Tifway and Riviera responded similarly to traffic and reached 50% green cover loss by 18.3 and 17.9 traffic events, respectively, which is consistent to work conducted by Trappe et al. (2011) and Goddard et al. (2008).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Tifway and Riviera responded similarly to traffic and reached 50% green cover loss by 18.3 and 17.9 traffic events, respectively, which is consistent to work conducted by Trappe et al. (2011) and Goddard et al. (2008).…”
Section: Resultssupporting
confidence: 90%
“…Cultivars of Cynodon spp. vary in traffic tolerance and adaptation to lower mowing heights (Hoyle et al., 2014; Trappe et al., 2011). Anecdotal evidence suggests that recently developed cultivars of bermudagrass [ Cynodon dactylon (L.) Pers.]…”
Section: Introductionmentioning
confidence: 99%
“…It was only after 20 further traffic events were applied to the same plots in the 2nd year that 'Tifway' had more cover than 'TifSport'. Trappe et al (2011) observed no difference in green turf color between 'Tifway' and 'TifSport' hybrid bermudagrass when assessed in the summer and fall. They found 'Tifway' and 'TifSport' to be within the top category in three of the four data assessment dates, the exception being in the Fall 2008 assessment date during which 'Tift No.…”
Section: Source Of Variationmentioning
confidence: 61%
“…Other research observed fall Tifway vegetative cover rating of 83% after 16 passes and 59% after 48 passes with the CTS (Goddard et al, 2008). Trappe et al (2011) observed fall Tifway percent green turf cover values ranging from 67 to 85.7% and summer values ranging from 92.5 to 93.8% after 40 passes with the CTS.…”
Section: Resultsmentioning
confidence: 87%